Electrochemical device and electronic device including the electrochemical device
By using a specific negative electrode active layer on the negative electrode electrode of the lithium-ion battery, the problem of insufficient dynamic performance and cycle characteristics of existing lithium-ion batteries is solved, and better low-temperature discharge characteristics and cycle life are achieved.
Patent Information
- Application Number
- JP2024554717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-03-21
AI Technical Summary
While existing lithium-ion batteries increase energy density and fast charging capabilities, their dynamic performance and cycle characteristics are limited, especially in low temperature conditions, with poor discharge characteristics.
By using a specific negative electrode active layer on the negative electrode electrode, the condition of A=W/(ID/IG) is satisfied, where 150≦A≦1000, the thermal generation peak of the negative electrode active layer does not exceed 450°C at room temperature, and the peak intensity ratios of 1350 cm-1 and 1580 cm-1 measured by Raman spectrum reflect the degree of surface defects.
It improves the dynamic and cyclic characteristics of lithium-ion batteries, improves the low-temperature discharge characteristics, and controls the thermal stability of the negative electrode active layer, extends the cycle life of the battery.
Smart Images

Figure 2025509536000001 
Figure 2025509536000002 
Figure 2025509536000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of energy storage, and in particular to electrochemical devices and electronic devices including such electrochemical devices. [Background technology]
[0002] For example, electrochemical devices such as lithium ion batteries have advantages such as high operating voltage, high energy density, environmental friendliness, stable cycle, and safety, and are therefore widely used in fields such as wearable devices, mobile phones, drones, and laptops. With the development of lithium ion batteries, the demand for lithium ion batteries suitable for mobile phones is also increasing, and in particular, lithium ion batteries need to have high energy density and fast charging capability at the same time. In response to this, the traditional approach is to select needle-shaped calcined coke with a relatively high capacity and prepare a negative electrode material through a series of processes such as crushing, graphitization, and surface modification treatment, but this method has limited effect on improving the dynamic properties of lithium ion batteries. Summary of the Invention
[0003] In response to the shortcomings of the prior art, the present invention provides an electrochemical device that meets the high capacity of the electrochemical device and enhances the kinetic and cycling properties of the battery. The present invention further provides an electronic device that includes the electrochemical device.
[0004] In a first aspect, the present invention provides an electrochemical device, the electrochemical device comprising a positive electrode, a separator, an electrolyte, and a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer provided on a surface of the negative electrode current collector, the electrochemical device satisfying A=W / (ID / IG) and 150≦A≦1000, and when measured by differential scanning calorimetry, the negative electrode active material layer has an exothermic peak in the range of room temperature to 450° C., and the peak area of the exothermic peak is W The Raman spectroscopy measurement revealed that the negative electrode active material layer had a 1350 cm -1and 1580cm -1 The present invention provides an electrochemical device having ID / IG, which is the ratio of the peak intensity of A to the peak intensity of I. Here, the ID / IG value can reflect the degree of surface defects in the negative electrode active material layer. In the present invention, the value of A is strongly related to the kinetic characteristics of the electrochemical device, and if the value of A is too small, it affects the exertion of the kinetic characteristics of the electrochemical device and deteriorates the low-temperature discharge characteristics. On the other hand, if the value of A is too high, it indicates that there are many active sites on the surface of the negative electrode active material layer, and by-products are easily formed, and therefore it affects the cycle life of the electrochemical device.
[0005] According to some embodiments of the invention, 150≦A≦750.
[0006] According to some embodiments of the invention, 20≦W≦490. In some embodiments of the invention, 100≦W≦300.
[0007] According to some embodiments of the invention, 0.13≦ID / IG≦0.54. In some embodiments of the invention, 0.13≦ID / IG≦0.52.
[0008] According to some embodiments of the present invention, the negative electrode active material layer has, as measured by DSC, the following: (d) when T1° C. is a heat generation start temperature of the negative electrode active material layer, T1 satisfies 100≦T1≦250; (e) when T2° C. is a first peak temperature of thermal decomposition of the negative electrode active material layer, T2 satisfies 140≦T2≦440; and (f) when T3° C. is a complete decomposition temperature of the negative electrode active material layer, T3 satisfies 400≦T3≦550. At least one of the above conditions is satisfied. According to some embodiments of the present invention, 100≦T1≦230. According to some embodiments of the present invention, 110≦T1≦205. According to some embodiments of the present invention, 150≦T2≦410. According to some embodiments of the present invention, 410≦T3≦450. In the present invention, the lower the temperatures of T1, T2, and T3, the easier it is for the negative electrode active material layer to decompose. This indicates that the worse the thermal stability, the lower the cycle capacity retention rate. However, at the same time, the number of active sites increases and the low-temperature discharge characteristics gradually improve, so controlling T1, T2, and T3 within the ranges limited by the present invention is advantageous for improving the cycle characteristics and low-temperature discharge characteristics of the electrochemical device.
[0009] According to some embodiments of the present invention, when the amount of heat generated per unit mass of the negative electrode active material layer is defined as P mW / mg, P satisfies 0.035≦P≦0.280.
[0010] According to some embodiments of the present invention, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or two of natural graphite and artificial graphite. According to some embodiments of the present invention, the negative electrode active material includes natural graphite.
[0011] According to some embodiments of the present invention, the negative electrode active material layer includes negative electrode active material particles having pores. According to some embodiments of the present invention, the negative electrode active material layer has a porosity of 20% to 50%.
[0012] According to some embodiments of the present invention, the electrolytic solution includes ethylene carbonate, propylene carbonate, and diethyl carbonate, and when the mass percentage of the ethylene carbonate is X%, the mass percentage of the propylene carbonate is Y%, and the mass percentage of the diethyl carbonate is Z% based on the mass of the electrolytic solution, X, Y, and Z satisfy 1.5≦X / Y≦8 and 2.5≦Z / Y≦25. In some embodiments of the present invention, 1.5≦X / Y≦8 and 3≦Z / Y≦15.
[0013] According to some embodiments of the present invention, X, Y, and Z satisfy 15≦X≦32, 3≦Y≦12, 30≦Z≦70. In some embodiments of the present invention, X, Y, and Z satisfy 16≦X≦30, 4≦Y≦11, 35≦Z≦60.
[0014] In a second aspect, the present invention provides an electronic device comprising an electrochemical device according to the first aspect above.
[0015] The negative electrode of the electrochemical device provided by the present invention contains a specific negative electrode active material layer, which allows the electrochemical device to have a high capacity and to have improved kinetic and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be further described below with reference to examples. It should be understood that these examples are used to illustrate the present invention and do not limit the scope of the present invention.
[0017] A first aspect of the present invention is an electrochemical device, the electrochemical device comprising a positive electrode, a separator, an electrolyte, and a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer provided on a surface of the negative electrode current collector, the electrochemical device satisfying A=W / (ID / IG) and 150≦A≦1000, wherein, when measured by differential scanning calorimetry, the negative electrode active material layer has an exothermic peak in the range of room temperature to 450° C., the peak area of the exothermic peak is WJ / g, and when measured by Raman spectroscopy, the negative electrode active material layer has an exothermic peak of 1350 cm -1 and 1580cm -1 The ratio of the peak intensity to the peak intensity of the ionized water is called ID / IG. The present invention provides an electrochemical device that achieves this. In the present invention, the value of A is strongly related to the kinetic characteristics of the electrochemical device, and if the value of A is too small, it affects the exertion of the kinetic characteristics of the electrochemical device and deteriorates the low-temperature discharge characteristics. On the other hand, if the value of A is too high, it indicates that there are many active sites on the surface of the negative electrode active material layer, and by-products are easily formed, thus affecting the cycle life of the electrochemical device.
[0018] In the present invention, 1350 cm -1 Peak intensities ID and 1580 cm -1 The peak intensity I G varies to some extent due to differences in measurement equipment. -1 ±50cm -1 and 1580cm -1 ±50cm -1 This can be understood as a peak intensity in the range of
[0019] According to some embodiments of the invention, the value of A may be 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000 and any value therebetween. According to some embodiments of the invention, 150≦A≦750.
[0020] According to some embodiments of the present invention, 20≦W≦490. According to some embodiments of the present invention, the value of W may be 20, 50, 100, 150, 200, 250, 300, 350, 400, 450, 490 and any value therebetween. According to some embodiments of the present invention, 100≦W≦300. When the value of A is within a limited range, the cycle characteristics and low temperature discharge characteristics of the electrochemical device are improved.
[0021] According to some embodiments of the present invention, 0.13≦ID / IG≦0.54. According to some embodiments of the present invention, the value of ID / IG may be 0.13, 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.52, 0.54, and any value therebetween. According to some embodiments of the present invention, 0.13≦ID / IG≦0.52. If the value of ID / IG is too large, it indicates that there are many defects in the negative electrode active material layer, which reduces the electronic conductivity of the negative electrode active material layer and affects the low-temperature discharge characteristics of the electrochemical device. If the value of ID / IG is too small, it may affect the ion conduction rate in the negative electrode active material layer and affect the low-temperature discharge characteristics of the electrochemical device.
[0022] According to some embodiments of the present invention, when measured by DSC, the negative electrode active material layer satisfies at least one of the following: (d) when the heat generation start temperature of the negative electrode active material layer is T1 ° C., T1 satisfies 100 ≦ T1 ≦ 250; (e) when the first peak temperature of thermal decomposition of the negative electrode active material layer is T2 ° C., T2 satisfies 140 ≦ T2 ≦ 440; and (f) when the complete decomposition temperature of the negative electrode active material layer is T3 ° C., T3 satisfies 400 ≦ T3 ≦ 550. In the present invention, the lower the temperatures of T1, T2, and T3, the more easily the negative electrode active material layer decomposes. This indicates that the worse the thermal stability, the lower the cycle capacity retention rate. However, at the same time, the number of active sites increases and the low-temperature discharge characteristics gradually improve, so that controlling T1, T2, and T3 within the ranges limited by the present invention is advantageous for improving the cycle characteristics and low-temperature discharge characteristics of the electrochemical device.
[0023] According to some embodiments of the present invention, T1 may be 100, 120, 140, 160, 180, 200, 220, 240, 250, and any value therebetween. According to some embodiments of the present invention, T2 may be 140, 180, 220, 260, 300, 340, 380, 420, 440, and any value therebetween. According to some embodiments of the present invention, T3 may be 400, 420, 460, 480, 500, 520, 540, 550, and any value therebetween. According to some embodiments of the present invention, 100≦T1≦230. According to some embodiments of the present invention, 110≦T1≦205. According to some embodiments of the present invention, 150≦T2≦410 According to some embodiments of the present invention, 150≦T2≦370. According to some embodiments of the present invention, 410≦T3≦450.
[0024] According to some embodiments of the present invention, when the heat generation amount per unit mass of the negative electrode active material layer is P mW / mg, P satisfies 0.035≦P≦0.280. According to some embodiments of the present invention, P may be 0.035, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.280, or any value therebetween.
[0025] According to some embodiments of the present invention, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or two of natural graphite and artificial graphite. According to some embodiments of the present invention, the negative electrode active material includes natural graphite. Different types of graphite exhibit different thermal stabilities, which in turn affect the thermal stability properties of the negative electrode active material layer. By selecting natural graphite or artificial graphite with different components and structures, the wettability of the electrolyte can be improved, the ion transmission path can be shortened, and the cycle characteristics and low-temperature discharge characteristics of the electrochemical device can be enhanced.
[0026] According to some embodiments of the present invention, the negative electrode active material layer includes negative electrode active material particles having pores. According to some embodiments of the present invention, the porosity of the negative electrode active material layer is 20% to 50%. According to some embodiments of the present invention, the porosity of the negative electrode active material layer may be 20%, 25%, 30%, 35%, 40%, 45%, 50% and any value therebetween. When the porosity of the negative electrode active material layer is within this range, it can ensure that the electrolyte has a relatively good wetting effect, which is favorable for the transmission of ions, and can improve the low-temperature discharge characteristics of the electrochemical device. On the other hand, when the porosity of the negative electrode active material layer is relatively large, it leads to the consumption of active lithium, which affects the cycle characteristics of the electrochemical device.
[0027] According to some embodiments of the present invention, the negative electrode current collector may include, but is not limited to, copper foil or aluminum foil.
[0028] According to some embodiments of the present invention, the electrolyte solution includes ethylene carbonate, propylene carbonate, and diethyl carbonate, and when the mass percentage of the ethylene carbonate is X%, the mass percentage of the propylene carbonate is Y%, and the mass percentage of the diethyl carbonate is Z% based on the mass of the electrolyte solution, X, Y, and Z satisfy 1.5≦X / Y≦8, 2.5≦Z / Y≦25. According to some embodiments of the present invention, 1.5≦X / Y≦8, 3≦Z / Y≦15. According to some embodiments of the present invention, X / Y may be 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, and any value therebetween. According to some embodiments of the present invention, Z / Y may be 2.5, 5, 7.5, 10, 12.5, 15, 17.5, 20, 22.5, 25, and any value therebetween. When the ethylene carbonate content, the propylene carbonate content, and the diethyl carbonate content satisfy the above relationship, a low-resistance SEI film is formed at the negative electrode interface, and the cycle characteristics and low-temperature discharge characteristics of the electrochemical device can be improved. On the other hand, when the relationship between the ethylene carbonate content, the propylene carbonate content, and the diethyl carbonate content does not satisfy the above limited relationship, the formed SEI film is unstable and easily destroyed, which may affect the cycle characteristics of the electrochemical device, or a relatively thick SEI film is formed, which increases the interface resistance of the negative electrode, affecting the low-temperature discharge characteristics of the electrochemical device.
[0029] According to some embodiments of the present invention, X, Y, and Z satisfy 15≦X≦32, 3≦Y≦12, and 30≦Z≦70. According to some embodiments of the present invention, X, Y, and Z satisfy 16≦X≦30, 4≦Y≦11, and 35≦Z≦60. According to some embodiments of the present invention, X is 15, 17.5, 20, 22.5, 25, 27.5, 30, 32, and the like. According to some embodiments of the present invention, Y may be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and any value therebetween. According to some embodiments of the present invention, Z may be 30, 35, 40, 45, 50, 55, 60, 65, 70, and any value therebetween. When the ethylene carbonate content, the propylene carbonate content, and the diethyl carbonate content satisfy the above relationship, the electrochemical device has better cycle characteristics and low-temperature discharge characteristics.
[0030] The electrolyte used in the electrochemical device of the present invention further comprises a lithium salt, an additive and other organic solvents.
[0031] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalato)borate LiB(C2O4)2 (LiBOB), or lithium difluoro(oxalato)borate LiBF2(C2O4) (LiDFOB). In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5 mol / L to 3 mol / L, 0.5 mol / L to 2 mol / L, or 0.8 mol / L to 1.5 mol / L.
[0032] In some embodiments, the additives include, but are not limited to, vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 1,3-propane sultone (PS), ethylene sulfate (DTD), 1,3-dioxane, maleic anhydride, adiponitrile, succinonitrile, 1,3,5-pentanetricarbonitrile, and 1,3,6-hexanetricarbonitrile.
[0033] In some embodiments, the other organic solvents include, but are not limited to, dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC).
[0034] The materials, configurations and methods of manufacture of the positive electrodes used in the electrochemical device of the present invention include those disclosed in any of the prior art.
[0035] According to some embodiments of the present invention, the positive electrode includes a current collector and a layer of a positive electrode active material located on the current collector. According to some embodiments of the present invention, the positive electrode active material includes, but is not limited to, lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese (NCM) ternary material, lithium iron phosphate (LiFePO4), or lithium manganate (LiMn2O4).
[0036] According to some embodiments of the present invention, the positive electrode active material layer further includes a binder and optionally includes a conductive material. The binder enhances the bonding between the positive electrode active material particles and enhances the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethyleneoxy-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluorovinyl, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, or the like. .
[0037] According to some embodiments of the present invention, the conductive material includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some examples, the carbon-based material includes natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, or any combination thereof. In some examples, the metal-based material includes metal powder, metal fiber, copper, nickel, aluminum, or silver. In some examples, the conductive polymer is a polyphenylene derivative.
[0038] According to some embodiments of the present invention, the positive electrode current collector may include, but is not limited to, aluminum foil.
[0039] The material and shape of the separator used in the electrochemical device of the present invention are not particularly limited and may be any technology disclosed in the prior art. In some embodiments, the separator comprises a polymer or inorganic material that is stable against the electrolyte of the present invention.
[0040] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, a film, or a composite film having a porous structure, and the material of the substrate layer is at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, the substrate layer may be a polypropylene porous film, a polyvinyl porous film, a polypropylene nonwoven fabric, a polyvinyl nonwoven fabric, or a polypropylene-polyvinyl-polypropylene porous composite film.
[0041] A surface treatment layer is provided on at least one surface of the base material layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.
[0042] The inorganic layer includes inorganic particles and a binder, the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate, and the binder includes at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polymethyl methacrylate, polytetrafluorovinyl, and polyhexafluoropropylene.
[0043] The polymer layer includes a polymer, and the polymeric material includes at least one of polyamide, polyacrylonitrile, acrylic ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene).
[0044] In some embodiments, the electrochemical device of the present invention includes, but is not limited to, any kind of primary battery, secondary battery, fuel cell, solar cell, or capacitance. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0045] The present invention further provides an electronic device comprising an electrochemical device according to the present invention. The electronic equipment or device of the present invention is not particularly limited. In some embodiments, the electronic equipment of the present invention includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copiers, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, minidisks, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, auxiliary bicycles, bicycles, lighting equipment, toys, game consoles, clocks, power tools, strobes, cameras, large household storage batteries, and lithium ion capacitors.
[0046] Hereinafter, the present invention will be described in more detail with reference to specific examples, taking the electrochemical device as a lithium ion battery as an example. EXAMPLES
[0047] 1. Preparation of Li-ion Batteries (1) Preparation of positive electrode The positive electrode active material, lithium cobalt oxide (LiCoO2), the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), were dissolved in N-methylpyrrolidone (NMP) solvent in a weight ratio of about 97.6:1.2:1.2, and mixed thoroughly to obtain a positive electrode slurry. The positive electrode slurry was then applied to an aluminum foil, which was a positive electrode current collector. The aluminum foil was dried, cold rolled, cut, slit, and dried to obtain a positive electrode piece.
[0048] (2) Preparation of negative electrode [1] Preparation of negative electrode active material Preparation of A1 raw material: At least one of needle-shaped raw coke, needle-shaped calcined coke, petroleum coke, asphalt coke, and forged coke was selected and pulverized until the particle size Dv50 (Dv50 indicates that 50% of the particles in the volume-based particle size distribution are smaller than this value) was 5 μm to 8 μm. The needle-shaped raw coke was then heated and treated at 300°C to 1200°C to obtain a precursor, which was then removed to obtain the A1 raw material.
[0049] Preparation of A2 raw material: Natural graphite ore is used, and crushing / ball milling and flotation are carried out to obtain natural flake graphite. The natural flake graphite is crushed, and powder with a particle size Dv50 of 6μm to 12μm is selected, and the powder is subjected to spheroidization to obtain A2 raw material.
[0050] A1 and A2 are mixed in a weight ratio of A1:A2=(0-100):(100-0), and a binder of 5%-30% of the weight of (A1+A2) is added and mixed until uniform, where the binder includes at least one of asphalt, phenolic resin, and epoxy resin with a softening point of 150°C, 200°C, 150°C, or 300°C, and is placed in a reactor, heated and stirred, and the temperature is set to 300°C-700°C, and then the mixture is placed in a graphitization oven and graphitized at 2500°C-3500°C. Finally, the graphitized finished product and the coating agent are mixed, and the mixture of the graphitized finished product and the coating agent is placed in a reactor, and surface treatment is performed at a temperature of 800°C-1500°C to obtain a negative electrode active material. The coating agent used here was a mixed phase consisting of 10% to 80% solvent and 1% to 50% novel carbon material, where the solvent contained at least one of toluene, ethanol, quinoline and ether, and the novel carbon material contained at least one of carbon nanotubes and graphene.
[0051] Taking Example 1 as an example, the process of preparing the negative electrode active material in the negative electrode preparation [1] will be specifically described. Preparation of A1 raw material: Select needle-shaped raw coke and crush it until the particle size Dv50 is 8 μm. Then, the needle-shaped raw coke was heated and treated at 1200°C to obtain a precursor, which was then taken out to obtain the A1 raw material.
[0052] Preparation of A2 raw material: Natural graphite ore was used, and crushing / ball milling and flotation were carried out to obtain natural flake graphite. The natural flake graphite was crushed, and powder with a particle size Dv50 of 8 μm was selected, and the spheroidization process was carried out to obtain A2 raw material.
[0053] A1 and A2 were mixed in a weight ratio of 4:1, and 25% of the weight of (A1+A2) was added and mixed until uniform. Here, the binder was selected from one or more of asphalt with a softening point of 200°C, or phenolic resin and epoxy resin, and mixed in a reactor, heated and stirred, and set at a temperature of 500°C, and then graphitized in a graphitization oven at 3000°C. Finally, the graphitized finished product and the coating agent were mixed and placed in a reactor, where they were surface-treated at a temperature of 1100°C to obtain a negative electrode active material. The coating agent used here was a mixture of 10% to 80% solvent and graphene in different ratios.
[0054] In the process of preparing the negative electrode active material in Example 1, by changing the types and amounts of materials used, the negative electrode active materials in Examples 2 to 35 and Comparative Examples 1 and 2 can be prepared.
[0055] [2] Preparation of negative electrode pieces: The negative electrode active material, styrene butadiene rubber (SBR) as a binder, and sodium carboxymethylcellulose (CMC) as a thickener were dispersed in deionized water in a weight ratio of 97.7:1.2:1.1, and mixed thoroughly until homogeneous. The mixture was then applied to a copper foil negative electrode current collector that had previously been coated with a conductive coating layer. The copper foil was then dried and cold-rolled to obtain negative electrode pieces.
[0056] (3) Preparation of separator A polyvinyl (PE) porous polymer film with a thickness of about 7 μm was used as the separator.
[0057] (4) Preparation of electrolyte In a glove box with an argon atmosphere and a water content of <10 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed uniformly, and LiPF6 with a mass percentage of 12% based on the mass of the electrolyte was added and mixed uniformly to obtain an electrolyte.
[0058] In Example 1, the weight percentage of ethylene carbonate was 15%, the weight percentage of propylene carbonate was 3%, and the weight percentage of diethyl carbonate was 70%.
[0059] The composition of the electrolytic solution in Examples 2 to 31, Comparative Examples 1 and 2 was the same as that in Example 1.
[0060] The electrolyte solutions in Examples 32 to 35 contained, in addition to EC, PC, and DEC shown in Table 2, DMC.
[0061] (5) Preparation of lithium-ion batteries The positive electrode pieces, separator, and negative electrode pieces were stacked in this order, and the separator was placed between the positive and negative electrodes to serve as an insulator, and then rolled up to obtain a bare cell. After the tabs were welded, the bare cell was placed in an aluminum plastic film exterior foil and dried, and the electrolyte prepared above was poured into the dried bare cell, and the bare cell obtained by rolling up was placed in the exterior. The lithium ion battery was obtained by injecting an electrolyte, packaging, forming, degassing, cutting, etc. The lithium ion batteries of the examples and comparative examples of the present invention were all prepared according to the above method.
[0062] 2. Measurement method (1) Measurement of low-temperature discharge maintenance rate After leaving the target battery at a measurement temperature of 25°C for 5 minutes, the lithium-ion battery was charged at a constant current of 1.5C to 4.48V, and then charged at a constant voltage of 0.05C at a voltage of 4.48V. It was further discharged at 0.5C to 3.0V, and the capacity at that time was recorded as C0. After that, the lithium-ion battery was charged at a constant current of 1.5C to 4.48V, and then charged at a constant voltage of 0.05C at a voltage of 4.48V, and then the battery was placed in an incubator at -20°C and discharged at a constant current of 0.5C to 3.0V, and the discharge capacity at that time was recorded as C1. The low-temperature discharge retention rate C1 / C0 was calculated in units of %.
[0063] (2) Measurement of cycle capacity retention rate After the subject battery was left to stand for 5 minutes at a measurement temperature of 45°C, the lithium-ion battery was charged at a constant current of 1.5C to 4.48V, and then charged at a constant voltage of 0.05C at a voltage of 4.48V. After standing for 5 minutes, the battery was discharged at a constant current of 1.0C to 3.0V, and then left to stand for 5 minutes. The capacity at that time was recorded as D0. The above charge and discharge process was repeated 500 times, and the final discharge capacity was recorded as D1. After cycling at 45°C, the capacity decay rate was D1 / D0, in %, and the unit was %.
[0064] (3) Measurement by differential scanning calorimetry (DSC measurement) According to the measurement standard of GB / T 13464-2008, the equipment of type STA449F3-QMS403C was used, and the temperature was set to increase from room temperature to 500°C at a heating rate of 0.1K / min to 50K / min. Preparation and measurement of samples: The lithium ion battery was fully discharged to 3.0V, the lithium ion battery was disassembled to take out the negative electrode active material layer, and placed in a crucible. The crucible containing the sample was then sealed and placed on the oven's baffle, and the measurement was started after stabilization for 20 minutes. After the measurement, the curve was subjected to time-temperature conversion, horizontal adjustment, and appropriately smoothed, and the peak value and enthalpy were assigned to obtain a DSC curve. From the DSC curve, the heat generation start temperature T1°C of the negative electrode active material layer, the first peak temperature T2°C of the thermal decomposition of the negative electrode active material layer, and the complete decomposition temperature T3°C of the negative electrode active material layer, as well as the heat generation amount P mW / mg per unit mass of the negative electrode active material layer and the peak area WJ / g of the heat generation peak can be obtained.
[0065] (4) Raman spectrum measurement Using a HR Evolution type laser confocal Raman microscope, the 1350 cm -1 Peak intensities ID and 1580 cm -1 The peak intensity IG of the negative electrode was measured, and the ratio of ID to IG, ID / IG, was calculated. The ID / IG value can reflect the degree of surface defects in the negative electrode active material layer.
[0066] (5) Measurement of porosity The true density was measured using an AccuPyCII 1340 true density measuring instrument in accordance with the measurement standard of GB / T 24586-2009. Preparation and measurement of samples: The negative electrode active material layer was processed into a small disk of a certain area, and the apparent volume V of the small disk was measured. The true density of this small disk was then measured using a true density measuring device to calculate the true volume V0. The ratio of the void volume of the sample to the total volume was calculated, and the void ratio was calculated as (V-V0) / V x 100%.
[0067] Using the above preparation method, Examples 1 to 18 and Comparative Examples 1 and 2 were prepared. The cycle characteristics of the lithium ion battery, such as the W value, ID / IG value, A value, and porosity of the negative electrode active material layer, were Table 1 shows the effect of the temperature on the charge transport and low-temperature discharge characteristics.
[0068] [Table 1]
[0069] As can be seen from Examples 1 to 18 and Comparative Examples 1 and 2 in Table 1, when the value of A, the value of W, the value of ID / IG, and the porosity of the active material layer are within the ranges defined by the present invention, the dynamic characteristics of the electrochemical device can be significantly improved, and the cycle characteristics and low-temperature discharge characteristics of the electrochemical device can be effectively improved.
[0070] Furthermore, Examples 19 to 31 were prepared using the above preparation method. Table 2 shows the type of negative electrode active material, the ID / IG value of the negative electrode active material layer, and the effects of thermal stability measured in a nitrogen gas protective atmosphere on the lithium ion battery cycle characteristics and low-temperature discharge characteristics.
[0071] [Table 2]
[0072] As can be seen from Example 7 and Examples 19 to 31, different types of graphite result in different electrochemical activity and thermal stability of the negative electrode active material layer. When the negative electrode active material layer contains at least one of natural graphite and artificial graphite, the characteristics of the electrochemical device can be improved. When the negative electrode active material layer contains natural graphite and artificial graphite, a synergistic effect is exerted between the two types of graphite, which reduces the consumption of active lithium and shortens the ion transmission path, resulting in the electrochemical device having better cycle characteristics and low-temperature discharge characteristics.
[0073] Furthermore, the above-mentioned preparation method was used to prepare Examples 32 to 35. Table 3 shows the effects of the composition and content of the electrolyte on the cycle characteristics and low-temperature discharge characteristics of the lithium-ion battery.
[0074] [Table 3]
[0075] As shown in Table 3, based on Example 29, the effects of ethylene carbonate, propylene carbonate and diethyl carbonate added to the electrolyte on the cycle capacity retention rate and low-temperature discharge retention rate of the electrochemical device were examined. As can be seen from Example 29 and Example 32 to Example 35, when the contents of ethylene carbonate, propylene carbonate and diethyl carbonate in the electrolyte solution satisfy the relationships of 1.5≦X / Y≦8, 2.5≦Z / Y≦25, 15≦X≦32, 3≦Y≦12 or 30≦Z≦70, an SEI film with low resistance is formed on the negative electrode surface, damage to the graphite structure of embedded ions is reduced, and the cycle characteristics and low-temperature discharge characteristics of the electrochemical device can be improved.
[0076] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the present invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the spirit, principle, and scope of the present invention.
Claims
1. 1. An electrochemical device comprising: The electrochemical device includes a positive electrode, a separator, an electrolyte, and a negative electrode; the negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on a surface of the negative electrode current collector, The electrochemical device satisfies A=W / (ID / IG) and 150≦A≦1000; When measured by differential scanning calorimetry, the negative electrode active material layer had an exothermic peak in the range of room temperature to 450° C., the peak area of the exothermic peak was W J / g, and the Raman spectrum was The negative electrode active material layer had a peak current of 1,350 cm -1 and the peak intensity at 1580 cm -1 The ratio of the peak intensity of the signal to the peak intensity of the signal is defined as ID / IG.
2. The electrochemical device of claim 1 , wherein the electrochemical device satisfies 150≦A≦750.
3. The electrochemical device comprises: (a) 20≦W≦490, (b) 100≦W≦300, and (c) 0.13≦ID / IG≦0.54 The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
4. When measured by DSC, the negative electrode active material layer was (d) when the heat generation start temperature of the negative electrode active material layer is T1° C., T1 satisfies 100≦T1≦250; (e) when the initial peak temperature of thermal decomposition of the negative electrode active material layer is T2° C., T2 satisfies 140≦T2≦440; (f) when the complete decomposition temperature of the negative electrode active material layer is T3° C., T3 satisfies 400≦T3≦550; and (g) When the heat generation amount per unit mass of the negative electrode active material layer is P mW / mg, P is , 0.035≦P≦0.280 is satisfied. The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
5. The negative electrode active material layer is (h) 110≦T1≦205, and (i) 150≦T2≦370 The electrochemical device according to claim 4 , wherein at least one of the following is satisfied:
6. The negative electrode active material layer contains a negative electrode active material, The negative electrode active material includes one or two of natural graphite and artificial graphite, 2. The electrochemical device of claim 1.
7. The negative electrode active material layer is (j) the negative electrode active material layer contains negative electrode active material particles having pores; and (k) the porosity of the negative electrode active material layer is 20% to 50%; The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
8. the electrolyte solution comprises ethylene carbonate, propylene carbonate, and diethyl carbonate; 2. The electrochemical device according to claim 1, wherein, based on the mass of the electrolytic solution, a mass percentage of the ethylene carbonate is X%, a mass percentage of the propylene carbonate is Y%, and a mass percentage of the diethyl carbonate is Z%, X, Y, and Z satisfy 1.5≦X / Y≦8 and 2.5≦Z / Y≦25.
9. 9. The electrochemical device according to claim 8, wherein X, Y, and Z satisfy 15≦X≦32, 3≦Y≦12, and 30≦Z≦70.
10. An electronic device comprising an electrochemical device according to any one of claims 1 to 9.
Citation Information
Patent Citations
Negative electrode material for non-aqueous secondary battery, negative electrode for non-aqueous secondary battery, and non-aqueous secondary battery
JP2020167141A
Negative electrode active material, electrochemical device using the same, and electronic device
JP2023517250A